-5(2x-9)=2(x-8)-12

Simple and best practice solution for -5(2x-9)=2(x-8)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2x-9)=2(x-8)-12 equation:


Simplifying
-5(2x + -9) = 2(x + -8) + -12

Reorder the terms:
-5(-9 + 2x) = 2(x + -8) + -12
(-9 * -5 + 2x * -5) = 2(x + -8) + -12
(45 + -10x) = 2(x + -8) + -12

Reorder the terms:
45 + -10x = 2(-8 + x) + -12
45 + -10x = (-8 * 2 + x * 2) + -12
45 + -10x = (-16 + 2x) + -12

Reorder the terms:
45 + -10x = -16 + -12 + 2x

Combine like terms: -16 + -12 = -28
45 + -10x = -28 + 2x

Solving
45 + -10x = -28 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
45 + -10x + -2x = -28 + 2x + -2x

Combine like terms: -10x + -2x = -12x
45 + -12x = -28 + 2x + -2x

Combine like terms: 2x + -2x = 0
45 + -12x = -28 + 0
45 + -12x = -28

Add '-45' to each side of the equation.
45 + -45 + -12x = -28 + -45

Combine like terms: 45 + -45 = 0
0 + -12x = -28 + -45
-12x = -28 + -45

Combine like terms: -28 + -45 = -73
-12x = -73

Divide each side by '-12'.
x = 6.083333333

Simplifying
x = 6.083333333

See similar equations:

| 6x^3-x^6-96x+16=0 | | 20=0.08x+8.75 | | cos(3x-75)=0.5 | | -v/5=45 | | 10x+20+90=180 | | -910a=26a | | Sin(15x)=15 | | 9y=9+27 | | 2(19-3a)=66-8a | | 2x^2+15x-50=22-x^2 | | 6(2+6b)-8(b+4)=-20 | | 66-8a=2(19-3a) | | (x^2-x)-14(x^2-x)+24=0 | | 2x+7=6x+31 | | y+8=0.5(x-3) | | 3w-12=-27 | | 2a^2=1+a | | (25x^2-100x+50)+(50x-50)(2x)-(20x)(5-5x)-50x^2=0 | | x-8=-3x+11 | | d(t)=(20+3t)t | | 2(2x+8)+4=4x+20 | | Y-1(12-2x)=6 | | 2x^2+7x-32=0 | | X+15=3x-75 | | 65-2c=-23 | | (30-1y)+1y=30 | | -140/21 | | -6x+10y=134 | | (25x^2-100x+50)(50x-50)(2x)-(20x)(-5)(5-5x)(-10x^2)=0 | | 180+7x=360 | | (20-2x)(10-2x)(x)= | | (25x^2-100x+50)(50x-50)(2x)-(20x)(-5)(5-5x)(10x^2)=0 |

Equations solver categories